LiuweiDihuang improved cognitive functions in SAMP8 mice by inhibiting COX-2 expression and subsequent neuroinflammation. (5th October 2022) - Song, Junying; Jia, Yaquan; Li, Junlin; Ding, Rui; Yuan, Yong; Cai, Ju; Su, Yunfang; Hua, Qian; Zhang, Zhenqiang
Abstract : Ethnopharmacological relevance: LiuweiDihuang (LW) pills was mainly used to treatment of children's fontanelle incomplete closure, enuresis and nervous system development delays and other diseases.Following the deepening of pharmacological research, LW has a good effect on neurological diseases include senile dementia. However, the neuroprotection mechanism of LW on Alzheimer's disease (AD) through regulation of inflammation remains unclear. Aim of the study: Here, we aimed to explore the effects and mechanism of LW on learning and memory deficits in SAMP8 mice. Materials and methods: Mice aged 6 months were treated with LW for 2 months and BV2, C6 and HT22 cells were treated with LW pharmaceutic serum and Lipopolysaccharide (LPS) continuously. Then, cognitive tests were performed, including the Morris water maze and Y maze tests. The mRNA level of cyclooxygenase 2 (COX-2) and pro-inflammatory factors (IL-1β, IL-6 and TNF-α) were examined in cells and the cortex and hippocampus by quantitative RT-PCR. The expression of postsynaptic density protein 95, synaptophysin and various inflammatory factors were detected in the cortex and hippocampus by Western blot. Furthermore, Ionized calcium binding adapter molecule 1, glial fibrillary acidic protein and Aβ were examined in the brain of AD mice by immunofluorescence staining and immunohistochemistry. And synaptic loss and neuronal ultrastructure were observed by transmission electron microscope. Results: We found that LW suppressed LPS-induced COX-2 expression in vitro. Importantly, LW dramatically improved spatial learning and memory in SAMP8 mice through inhibiting Aβ accumulation and restoring structural synaptic integrity. Furthermore, LW inhibited the glial activation and neuroinflammation (COX-2, IL-1β, IL-6 and TNF-α) in the cortex and hippocampus of SAMP8 mice. Conclusion: Taken together, the present data not only indicated that LW is an effective agent on improving the learning and memory deficits through mitigating neuroinflammation but highlighted the LW can be a potential therapeutic drug for AD therapy. Graphical abstract: Image 1